Sustainable finance: The impact of selected green bonds on issuing firms' greenhouse gas emission (GHG) levels in selected ASEAN countries - Bautista, Jomabelle C. (Animo Repository, 2023)
Transitioning to a low-carbon economy necessitates the advancement of sustainable finance through the use of efficient financial tools. Although green bonds are still in their infancy, investors hesitate to invest in them because of greenwashing. This research seeks to determine the effect of green bonds on greenhouse gas (GHG) emission levels to improve investor decision-making and the growth of the green bond market. The study also examines the correlation between the size of the emitting company and its claimed GHG emission levels. This paper employed a quantitative-correlational research approach to investigate the effect of green bonds on the environmental performance of enterprises in Malaysia, Indonesia, and Thailand, as measured by their stated GHG emission levels. The research used criterion sampling to collect secondary data from 17 green bonds issued between 2018 and 2022. The data was collected through Refinitiv Eikon, Asianbondsonline, the Indonesia Central Securities Depository, the Corporate Registry, peer-reviewed journals, and annual reports found on the official websites of respondent companies. The correlational method was employed to examine and evaluate the statistical association between the issue of green bonds and the environmental performance of businesses. Utilizing a random effects model, the study found that green bond issuance did not improve the environmental performance of Malaysian and Indonesian enterprises in terms of their stated GHG emission levels. Nonetheless Thai companies reported a large increase in GHG emissions after issuing bonds. The study's findings indicate the necessity for additional investigation into the causes of the lack of influence of green bond issues on environmental performance.